Informed consent in clinical trials with reference to information disclosure to patient-subjects - Yusof, Yuhanif; Che Ngah, Anisah; Mohamad Zaher, Zaki Morad (Department of Community Health, Universiti Kebangsaan Malaysia Medical Center, 2014)
Introduction The aim of this study was to examine the aspect of information disclosure by doctor investigator during the process of obtaining informed consent in clinical trials.Methods This research employed a mixed-method data collection that is library research and interview.A qualitative methodology and analysis were used in an open-ended, face-to-face interviews with 17 patient-subjects.The interview questions were based on information that needed to be disclosed to patient-subjects during the process of obtaining informed consent.Each interview took place in Kajang Hospital and National Heart Institute and lasted 25-30 minutes. Interviews were conducted in Bahasa Melayu and English.The interviews were tape-recorded, and the main points from the interviews were jotted down to ensure that all information was adequately gathered. Interviewed occurred in Kajang Hospital and National Heart Institute.The participants were patients who had been referred to the Kajang Hospital and National Heart Institute.They were recruited (8 from Kajang Hospital and 9 from National Heart Institute) by their own doctors to participate in a study to evaluate the safety and effectivenes of the investigational stent after been diagnosed with coronary artery disease and also in a study to investigate drug for antidepressant. respectively.Results The study revealed that doctor-investigators fail to disclose full information to patient-subjects. Instead, doctor-investigators only disclosed information which they thought were necessary for the patient-subjects to know.The study also showed that there were doctor-investigators who did not disclose information at all to the patient-subjects.Conclusions This study implies that the aspect of information disclosure in the process of obtaining informed consent in clinical trials is rather poor and did not fulfill the criterion of good medical practice.A random monitoring task to be conducted by the research ethics commitees during the informed consent process is suggested.